Digital Storytelling Implementation with Code Mixing (English-Indonesia) for Enhancing Students' Speaking Ability at The Eight Graders - Isnaniah Isnaniah; Khilda Shopia; Syifa Fadhilah Hamid; Purnawati Purnawati (JETL (Journal of Education, Teaching and Learning), 2023)
One alternate way for making English more attractive is digital storytelling. Cooperative learning is essential when dealing with youngsters of varying levels and intellect. The method used in this study is experimental. The researcher used the experiential technique to study the cause-effect relationship. Based on the outcomes of the initial presentation, it was found that the difference in the average pretest and posttest scores from the implementation of digital Storytelling With Code Mixing (English-Indonesian) improved the speaking ability of eighth-grade students. The average score attained, known by the posttest, is higher than the average score on the pretest. Because of sig. (2-tailed) is a little less to = 0.05 (sig. 2-tailed = 0.002 0.05), H0 is rejected. So it can be concluded that there has been an increase in the speaking ability of eighth-grade students after implementing digital Storytelling With Code Mixing (English-Indonesian). It shows that the existence of a digital Storytelling With Code Mixing (English-Indonesian) program will enhance the speaking skills.